1999
DOI: 10.1152/jn.1999.82.3.1497
|View full text |Cite
|
Sign up to set email alerts
|

Quantal Unit Populations at theDrosophilaLarval Neuromuscular Junction

Abstract: Focal extracellular recording at visualized boutons of the Drosophila larval neuromuscular junction was used to determine frequency and time course of the spontaneously occurring quantal events. When simultaneous intracellular recordings from the innervated muscle cell were made, more than one class of quantal event occurred at some of the individual boutons. "True" signals (arising at the bouton within the focal macropatch electrode) were often contaminated by additional signals generated outside the lumen of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…This difference in vesicle diameter leads to a ϳ70% increase in vesicle volume and a corresponding increase in quantal size (Karunanithi et al 2002). These same authors also showed that some individual synaptic boutons exhibited more than one class of quantal event (Wong et al 1999). Proteins that regulate vesicle formation may change vesicle size (for review, see Murthy and De Camilli 2003).…”
Section: Discussionmentioning
confidence: 98%
“…This difference in vesicle diameter leads to a ϳ70% increase in vesicle volume and a corresponding increase in quantal size (Karunanithi et al 2002). These same authors also showed that some individual synaptic boutons exhibited more than one class of quantal event (Wong et al 1999). Proteins that regulate vesicle formation may change vesicle size (for review, see Murthy and De Camilli 2003).…”
Section: Discussionmentioning
confidence: 98%
“…By increasing the extracellular volume at the synapse, it may also provide a “sink” into which released glutamate can diffuse to terminate synaptic responses15. The SSR may filter the electrophysiological consequences of receptor activation35 or otherwise alter electrical signals36. The SSR is also closely associated with ribosomes and may be a site of local glutamate receptor translation37.…”
Section: Discussionmentioning
confidence: 99%
“…14,39 Briefly, wandering third instar larvae were dissected in ice-cold Schneider's insect medium (Sigma-Aldrich, Cat. No.…”
Section: Electrophysiologymentioning
confidence: 99%